X-ray fluorescence and couplet thickness data from core SL-01-RS, Paraná Basin, Brazil - Marcus Kochhann (PANGAEA, 2019)
XRF-derived TiO2 and Fe2O3 records measured at 2 cm sampling interval with a handheld XRF spectrometer at core SL-01-RS. Couplet thickness record with measurements centered at central coupled depth.